IMPLEMENTASI CORPORATE CULTURE “AKHLAK” DALAM UPAYA MENINGKATKAN KINERJA KARYAWAN DI MASA PANDEMI COVID-19 (STUDI PADA PT JASA MARGA BELMERA) - Muhammad Wisnu Wijaya Aditama; Dharmawan Sriyanto; Nicholas Marpaung (DFAME Digital Financial Accounting Management Economics Journal, 2023)
Company culture refers to the values and norms within an organization that serve as guidelines for employees. State-owned enterprises (BUMN) need to innovate to compete with private companies, including the transformation of human resources. In Indonesia, BUMNs like PT Jasa Marga Belmera adopt the "AKHLAK" culture as the core values of the company. This research evaluates the implementation of the AKHLAK culture in enhancing employee performance during the Covid-19 pandemic. A qualitative research method is employed, involving interviews, observations, and documentation. The research findings indicate that the strategy and implementation of AKHLAK are functioning well, although there is still room for improvement in raising employee awareness of the company's culture. The implementation of AKHLAK has a positive impact on both employee and company performance.